Conceptual Framework for Lightning Risk Management in Substations Based on Multi-Layered Protection - Sing, Krisna (Cattleya Darmaya Fortuna, 2025)
This article presents a conceptual framework for lightning risk management at substations that emphasizes a defense-in-depth approach as the primary strategy for technical and operational risk reduction. The proposed framework integrates an understanding of lightning hazard (strike density, local climate, topography), asset vulnerability (isolation coordination, clearances, and BIL per equipment), and failure consequences (service reliability, safety, CAPEX/OPEX costs) into a standards-based risk management cycle. The protection layers are conceptualized from external mitigation (shielding/air-termination, down-conductors, and low-impedance grounding systems), internal protection (surge arresters and insulation coordination), to detection and control layers (lightning current monitoring, event recording, condition-based maintenance). The framework also maps the process of establishing target protection levels using the ALARP risk matrix, conceptually determining arrester locations/powers, and the governance of technical inspections and audits throughout the asset lifecycle. Integration of substation digital data (IEC 61850) to improve event observability and maintenance policy feedback is also proposed. While remaining theoretical (without calculations), this framework provides systematic guidance for utilities in developing layered protection policies that are adaptive to tropical climate variability, budget constraints, and reliability demands, while also serving as a basis for further quantitative studies